2018
DOI: 10.1007/s00167-018-5128-7
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of patellofemoral cartilage status after medial open-wedge high tibial osteotomy

Abstract: Level IV, therapeutic case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
72
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 28 publications
2
72
2
1
Order By: Relevance
“…4,5 Moreover, Lee et al 8 suggested that overcorrection, which indicated a higher correction angle, could induce patellofemoral degenerative progression. Similarly, Tanaka et al 7 reported that cartilage injuries in the patellofemoral joints tended to progress after OWHTO in the knees, with medial open gap 13 mm, or with a change in the medial proximal tibial angle 9 . Javidan et al 5 investigated the impact of OWHTO on the patellofemoral joints in cadaveric knees and reported that the contact pressure of the patellofemoral joint significantly increased in the knees with a medial opening gap of 10 mm.…”
Section: See Related Article On Page 1703mentioning
confidence: 88%
See 4 more Smart Citations
“…4,5 Moreover, Lee et al 8 suggested that overcorrection, which indicated a higher correction angle, could induce patellofemoral degenerative progression. Similarly, Tanaka et al 7 reported that cartilage injuries in the patellofemoral joints tended to progress after OWHTO in the knees, with medial open gap 13 mm, or with a change in the medial proximal tibial angle 9 . Javidan et al 5 investigated the impact of OWHTO on the patellofemoral joints in cadaveric knees and reported that the contact pressure of the patellofemoral joint significantly increased in the knees with a medial opening gap of 10 mm.…”
Section: See Related Article On Page 1703mentioning
confidence: 88%
“…Conversely, several studies have highlighted that the patellofemoral OA progression after OWHTO did not affect clinical outcomes. 3,7,9 In my experience, despite the progression of patellofemoral OA after OWHTO, there are few cases of anterior knee pain. 3 I have two reservations about the study of Lee et al, 8 and the conclusions must be interpreted with caution.…”
Section: See Related Article On Page 1703mentioning
confidence: 88%
See 3 more Smart Citations